The university in its place : social and cultural perspectives on the regional role of universities /: social and cultural perspectives on the regional role of universities. ([2018]) - Brennan, John, 1947-; Cochrane, Allan; Lebeau, Yann; (Researcher in higher education), Williams, Ruth
No abstract available